2004
DOI: 10.1159/000078737
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Criteria for the Activity of Crohn’s Disease by Power Doppler Sonography

Abstract: Background/Aim: In recent years, power Doppler sonography has been proposed as a method to assess disease activity in patients with Crohn’s disease. The aim of this prospective study was to evaluate diagnostic criteria for power Doppler sonography by blinded comparison with ileocolonoscopy. Methods: Twenty-two patients with confirmed Crohn’s disease were prospectively investigated with B-mode and power Doppler sonography (HDI 5000, Philips Ultrasound) as well as ileocolonoscopy. Sonography was performed within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(62 citation statements)
references
References 22 publications
0
58
0
4
Order By: Relevance
“…Data on staging disease activity in CD are lacking for these techniques; by using the same inclusion criteria as we described above, only one article on power Doppler sonography [34] would be eligible for analysis (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Data on staging disease activity in CD are lacking for these techniques; by using the same inclusion criteria as we described above, only one article on power Doppler sonography [34] would be eligible for analysis (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Although a number of authors have described the utility of color Doppler imaging in gastrointestinal disorders, particularly CD, celiac disease and mesenteric artery stenosis, its exact role in diagnosis and/or monitoring disease activity remains to be investigated further. In a trial with 22 patients with confirmed CD, a high concordance between a power Doppler ultrasound score (measuring vascularization) and the degree of local inflammation assessed with an endoscopic severity score was demonstrated with values from 0.83 to 0.98 [34] . A pilot study prospectively involving 20 patients demonstrated a highly significant correlation between the mean blood vessel density assessed by power Doppler sonography and the semiquantitative score tested by Limberg showing its potential application in routine clinical practice [35] .…”
Section: Color Doppler Imagingmentioning
confidence: 94%
“…Increased intramural vascularization is another US parameter for IBD, and it can be evaluated by Doppler ultrasound [42]. It is also a marker of active inflammation and is well correlated with endoscopic findings and CDAI [35,43]. The quantification of the degree of inflammation in this case is difficult, considering that the transmural vascularization is related to many factors, including the ingestion of food.…”
Section: Ultrasoundmentioning
confidence: 99%
“…Doppler examination of the vascularization of thickened bowel wall is useful for the differentiation of relapse from remission and is well correlated with endoscopic findings both in adults, and children [35,43,71]. For the evaluation of microvascularization, CEUS accuracy is comparable to MRI accuracy and superior to Doppler ultrasound [76].…”
Section: Monitoringmentioning
confidence: 99%